2014
DOI: 10.1007/s11606-014-2946-2
|View full text |Cite
|
Sign up to set email alerts
|

Financial Exploitation of Older Adults: A Population-Based Prevalence Study

Abstract: One-year period FEOA prevalence was 2.7% (95% CI, 2.29-3.29) and lifetime prevalence was 4.7% (95% CI, 4.05-5.34). Greater relative risk (RR) of one-year period prevalence was associated with African American/black race (RR, 3.80; 95 % CI, 1.11-13.04), poverty (RR, 1.72; 95 % CI, 1.09-2.71), increasing number of non-spousal household members (RR, 1.16; 95 % CI, 1.06-1.27), and ≥ 1 instrumental activity of daily living (IADL) impairments (RR, 1.69; 95 % CI, 1.12-2.53). Greater RR of lifetime prevalence was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 14 publications
3
93
1
4
Order By: Relevance
“…Acierno et al 1 found that 11.4 % of elders reported at least one incident of abuse over the past year, including neglect, emotional, physical and sexual abuse. The present study by Peterson et al 2 highlights another form of abuse, financial abuse, and finds that it is likewise far too common.…”
contrasting
confidence: 47%
“…Acierno et al 1 found that 11.4 % of elders reported at least one incident of abuse over the past year, including neglect, emotional, physical and sexual abuse. The present study by Peterson et al 2 highlights another form of abuse, financial abuse, and finds that it is likewise far too common.…”
contrasting
confidence: 47%
“…For example, in a recent study involving a weighted sample of more than 4000 older adults in New York State, 4.7% of participants reported experiencing some form of financial exploitation since turning age 60 years (6). This estimate is probably conservative because the study used telephone interviews, thereby excluding participants with substantial cognitive and other impairments that are potential risk factors.…”
Section: Epidemiology Of Aafv: Prevalence and Risk Factorsmentioning
confidence: 99%
“…These results will provide health professionals and researchers in the field of gerontology with information regarding the choice of instruments for the evaluation of this construct, as well as knowledge of the studies that support the instruments in populations of elderly people with or without cognitive impairment. It should be noted that deficits in the ability to manage one's own finances may be a sign of cognitive impairment and should be considered in the clinical evaluation of the elderly 7,[36][37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…Some abilities can remain stable in this period, such as naming coins/banknotes, and understanding and prioritizing bills 18 . Professionals who work with the elderly must understand and identify the reduction of the financial decision-making capacity of such individuals and assist them in order to reduce potential financial abuse and improper exploitation 8,37,52 .…”
Section: The Studies By Daniel Marson Et Al Are Especially Notable Imentioning
confidence: 99%